SPK: ANALISA REKOMENDASI BANK KONVENSIONAL DENGAN PROMETHEE SEBAGAI SOLUSI CERDAS UNTUK MENABUNG - Tri Novika; Afrialita Widiastari; Viya Miralda; Agus Perdana Windarto (JUSIM (Jurnal Sistem Informasi Musirawas), 2018)
Many banks in Indonesia, both government and private offer different advantages to customers, so there are still many common people who are hesitant in deciding where to save. The reasearch proposes a decision support system to recommend conventional banks as a savvy solution for saving. The promethee method generates decisions by comparing alternatives based on different preference functions and weights of each criterion in which the decision result is determined from the promethee II (net flow) rating. The criteria used as the valuation for conventional bank are savings interest rate (C1), number of ATM machine (C2), initial deposit of saving (C3), monthly administration fee (C4) and bank service (C5). This developed system resulted Bank Mandiri as recommendation of conventional bank as smart solution to save with net value 0,725. With this system can help prospective customers in determining the ideal saving place to prepare for future needs.